Acceptance of the Implementation of Islamic Sharia Laws in West Aceh, Indonesia - Manan, Abdul (KnE Social Sciences, 2020)
Aceh is the only Province in Indonesia that is authorized by the Indonesian central government to implement Islamic sharia laws. The basic legal framework that made this possible was provided after the Peace Treaty concluded on 15th August 2005 following the Tsunami disaster of 26 December 2004, which built on the Special Autonomy Laws for Aceh of 1999 and 2001. This study describes and critically analyses the social reality of implementation of Islamic sharia in West Aceh using an ethnographic approach. The latter is a research form that focuses on the meaning of socio-cultural phenomena through meticulous observations. The study used three different ways of data col-lection, viz; interviews, observations and documents. Thus, the data used was in the form of quotes, descriptions, and documents. The results showed that the implementation has evoked many perceptions. The current implementation of Islamic sharia in West Aceh is running well considering the essential role of local government. Furthermore, the government itself has done various programs related to the implementation of Islamic sharia laws. However, a number of people still believe that the current condition of sharia in West Aceh has not yet provided the expected results since there is still much unislamic behavior observable in public and many teenagers’ attitudes are not yet in line with Islamic values and teachings. The public perceptions, responses, and values are that the implementation of Islamic sharia laws in West Aceh has still not met expectations due to various problems. Keywords: social facts, implementation of Islamic sharia laws, West Aceh District